Basic Needs and Self-Actualization of Baek Kang-Hyeok in the Korean Drama The Trauma Code: Heroes on Call - Lailatun Nadifah; Fafi Inayatillah (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The purpose of this study is to analyze Baek Kang-Hyeok's basic needs and self-actualization needs, as well as to motivate the surrounding community when fulfilling these needs, from the most basic to the fulfillment of self-actualization needs. Basic needs are indicated by physiological needs, safety needs, belonging needs, and esteem needs. Furthermore, higher needs are the self-actualization needs of Baek Kang-Hyeok in the Korean drama "The Trauma Code: Heroes on Call," using Abraham Maslow's theory (1954). This research method uses descriptive qualitative research with data sources from the Korean drama "The Trauma Code: Heroes on Call." The research data consists of words, scene documentation, and sentences. Data collection techniques include preparing data sources, listening techniques, documentation techniques, note-taking techniques, grouping data, coding, and data reduction. The results show Baek Kang-Hyeok's achievement in basic physiological needs such as food, drink, shelter, and sleep. Safety needs include physical safety, freedom from fear or worry, security in having a job and a steady salary. He also needs a sense of belonging to colleagues who assist him during surgery. Esteem needs include success, self-confidence, fame, status, and recognition. Self-actualization needs include empathy, helpfulness, a medical profession that saves patients, talents or hobbies, and problem-solving skills. Once basic needs and self-actualization are met, a person will demonstrate psychological stability, leading to motivation to fulfill higher-order needs and become a better person. This study recommends further research related to Abraham Maslow's theory in the context of fulfilling basic needs and self-actualization in the realms of work, well-being, mental health, and social needs.